2017
DOI: 10.1002/hbm.23610
|View full text |Cite
|
Sign up to set email alerts
|

Limbic grey matter changes in early Parkinson's disease

Abstract: The purpose of this study was to investigate local and network-related changes of limbic grey matter in early Parkinson's disease (PD) and their inter-relation with non-motor symptom severity. We applied voxel-based morphometric methods in 538 T1 MRI images retrieved from the Parkinson's Progression Markers Initiative website. Grey matter densities and cross-sectional estimates of age-related grey matter change were compared between subjects with early PD (n 5 366) and age-matched healthy controls (n 5 172) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 64 publications
5
11
0
Order By: Relevance
“…This is in line with case‐control and large cohort studies indicating no extranigral morphological and diffusivity changes in cognitively unimpaired early‐stage parkinsonian patients without burdensome neuropsychiatric manifestations, although early diffusivity changes are present in the substantia nigra and may correlate with motor and nonmotor manifestations, albeit inconsistently . Furthermore, 2 recent findings support that alteration in global connectivity may occur in the early stage of Parkinson's disease, pointing to a subnetwork of limbic structures (notably the right amygdala), and may associate with cognitive impairment and autonomic dysfunction but not anxiety, whereas apathy and depression were not evaluated . Here, we demonstrate that early microstructural alterations related to apathy involve a bilateral and selective network of interconnected cortical and subcortical structures belonging to the corticostriatopallidothalamic limbic loop including the medial frontal cortex, subgenual and pregenual anterior cingulate cortex, ventromedial caudate nucleus, globus pallidus, and medial thalamus.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in line with case‐control and large cohort studies indicating no extranigral morphological and diffusivity changes in cognitively unimpaired early‐stage parkinsonian patients without burdensome neuropsychiatric manifestations, although early diffusivity changes are present in the substantia nigra and may correlate with motor and nonmotor manifestations, albeit inconsistently . Furthermore, 2 recent findings support that alteration in global connectivity may occur in the early stage of Parkinson's disease, pointing to a subnetwork of limbic structures (notably the right amygdala), and may associate with cognitive impairment and autonomic dysfunction but not anxiety, whereas apathy and depression were not evaluated . Here, we demonstrate that early microstructural alterations related to apathy involve a bilateral and selective network of interconnected cortical and subcortical structures belonging to the corticostriatopallidothalamic limbic loop including the medial frontal cortex, subgenual and pregenual anterior cingulate cortex, ventromedial caudate nucleus, globus pallidus, and medial thalamus.…”
Section: Discussionsupporting
confidence: 83%
“…31,32 Furthermore, 2 recent findings support that alteration in global connectivity may occur in the early stage of Parkinson's disease, pointing to a subnetwork of limbic structures (notably the right amygdala), and may associate with cognitive impairment and autonomic dysfunction but not anxiety, whereas apathy and depression were not evaluated. 33,34 Here, we demonstrate that early microstructural alterations related to apathy involve a bilateral and selective network of interconnected cortical and subcortical structures belonging to the corticostriatopallidothalamic limbic loop [35][36][37] including the medial frontal cortex, subgenual and pregenual anterior cingulate cortex, ventromedial caudate nucleus, globus pallidus, and medial thalamus. Moreover, whitematter abnormalities in the anterior interhemispheric and frontal projection tracts correlated with the severity of apathy, which supports the role of selective disorganization of reciprocal corticocortical, corticothalamic, and corticostriatopallidothalamic connections in apathy affecting parkinsonian patients.…”
Section: Discussionmentioning
confidence: 66%
“…Pathological study of the amygdala in advanced Parkinson's disease subjects has identified a selective pattern of degeneration localized to the corticomedial and basolateral formation and an association between pathological load in the laterobasal amygdala and visual hallucinations (49). MRI studies of the amygdala in Parkinson's disease have contributed mixed findings to date; reporting no difference between Parkinson's disease and control subjects (90) or slightly reduced volume of the right amygdala in Parkinson's disease relative to healthy controls (91,92). The current study reports significant atrophy in advanced Parkinson's disease relative to early Parkinson's disease and healthy control subjects, a finding which has not previously been reported using MRI methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Three hundred and ninety-two PD MRI T1 structural images were initially used in this study. All MRI image data were obtained from the PPMI website ( http://www.ppmi-info.org /) on 13/10/2015 as previously published ( Li et al, 2017 ). Also, the UPRDS III scores for these subjects were obtained from the PPMI database.…”
Section: Methodsmentioning
confidence: 99%
“…It is mathematically easy to calculate, but difficult to interpret the correlation between the GM and UPDRS III score in healthy controls. Also, it is biologically not meaningful as these scores define the presence and the severity of symptoms rather than the degree of loss of normal function ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%